Combination Fractional Carbon Dioxide Laser Treatment and Bone Marrow Mesenchymal Stem Cell Therapy Enhances the Treatment of Skin Photoaging in a Murine Model System - Li L; He Z; Yu C; Zhang C; Yu Y; Li Y; Xu X (Clinical, Cosmetic and Investigational Dermatology)
Li Li,1– 3,* Zeyu He,3– 5,* Chengqian Yu,3– 5 Chao Zhang,3– 5 Yanqiu Yu,6 Yuanhong Li,3– 5 Xuegang Xu3– 5 1ShanXi Medical University, Taiyuan, People’s Republic of China; 2Department of Dermatology, The First Hospital of ShanXi Medical University, Taiyuan, 030001, People’s Republic of China; 3Department of Dermatology, The First Hospital of China Medical University, Shenyang, 030001, People’s Republic of China; 4Key Laboratory of Immunodermatology (China Medical University), Ministry of Education, Shenyang, 110001, People’s Republic of China; 5NHC Key Laboratory of Immunodermatology (China Medical University), Shenyang, 110001, People’s Republic of China; 6Department of Pathophysiology, College of Basic Medical Science, China Medical University, Shenyang, 110122, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xuegang Xu, Department of Dermatology, The First Hospital of China Medical University, No. 155 Nanjing Bei Street, Heping District, Shenyang, Liaoning Province, 110001, People’s Republic of China, Email xuxuegang2749290@163.com Li Li, Department of Dermatology, The First Hospital of ShanXi Medical University, No. 85 South Jiefang Road, Yingze District, Taiyuan, Shanxi Province, 030001, People’s Republic of China, Email lilizaimu0807@163.comBackground: Fractional carbon dioxide lasers and bone marrow mesenchymal stem cells (BMSCs) are commonly employed in the treatment of skin photoaging.Objective: This study was developed to explore the effects of combination carbon dioxide laser treatment and BMSC injection on skin photoaging and the underlying molecular mechanisms.Methods & Materials: In total, 24 mice with experimentally photoaged skin were separated into control, carbon dioxide fractional laser treatment, combination therapy, and BMSC injection groups. Samples of dorsal skin from these animals were subjected to hematoxylin and eosin staining or Masson’s trichrome staining. In addition, immunohistochemical analyses and real-time polymerase chain reaction analyses were conducted to detect MMP-3 and MMP-9 expression.Results: After 1 week, both dermal thickness and collagen fiber density were significantly increased in the BMSC and combination treatment groups as compared to the control group (P< 0.05), while both of these parameters were significantly increased in all treatment groups after 4 weeks relative to the control group (P< 0.05), with the most pronounced effect in the combination therapy group (P< 0.05). MMP-3 and MMP-9 mRNA and protein levels in the treatment groups were decreased relative to the control group after 4 weeks.Conclusion: Combination BMSC and carbon dioxide laser therapy was more effective than either of these therapeutic approaches in isolation as a treatment for photoaged skin. The improvement of effect may be due to the decrease of MMP-3 and MMP-9 expression in combination therapy.Keywords: bone marrow mesenchymal stem cell, fractional carbon dioxide laser, photoaging, matrix metalloproteinase, mouse model